Unhealthy lifestyle associated with higher intake of sugar-sweetened beverages among Malaysian school-aged adolescents - Gan, Wan Ying; Mohamed, Siti Fathiah; Law, Leh Shii (MDPI, 2019)
High consumption of sugar-sweetened beverages (SSBs) among adolescents has turned into a global concern due to its negative impact on health. This cross-sectional study determined the amount of SSB consumption among adolescents and its associated factors. A total of 421 adolescents aged 13.3 ± 1.3 years (41.8% males, 58.2% females) completed a self-administered questionnaire on sociodemographic characteristics, physical activity, screen-viewing behavior, sleep quality, frequency of eating at fast food restaurants, home food availability, peer social pressure, parenting practice, and SSB consumption. Weight and height were measured. Results showed that the mean daily consumption of SSBs among adolescents was 1038.15 ± 725.55 mL. The most commonly consumed SSB was malted drink, while the least commonly consumed SSB was instant coffee. The multiple linear regression results revealed that younger age (β = −0.204, p < 0.001), higher physical activity (β = 0.125, p = 0.022), higher screen time (β = 0.147, p = 0.007), poorer sleep quality (β = 0.228, p < 0.001), and unhealthy home food availability (β = 0.118, p = 0.032) were associated with a higher SSB intake. Therefore, promoting a healthy lifestyle may help to reduce the excessive consumption of SSBs among adolescents.